Meteorological observations (temperature, relative humidity and rainfall) at the volcanic crater of Agnano (Campi Flegrei - Naples - Italy) during the period Jan. 2022 - Dec. 2022 - Fortelli, Alberto (PANGAEA, 2023)
Weather data monitoring is ongoing since March 2021 in Agnano, near Naples (Italy). The dataset includes thermo-hygrometric and pluviometric parameters, acquired at the Agnano automatic weather station (Model: DAVIS Instruments - Vantage Pro2 wireless) during the period January 2022 - December 2022. The weather station is managed by Ippodromi Partenopei S. r. l. The data transfer from the weather station to remote server is performed by an Internet LAN connection. The main aim of this activity is to acquire rainfall dataseries in order to analyze the influence of pluviometry on recurrent volcanic seismic and/or microseismic activity (tremors) and landslides in the geographical area of Campi Flegrei.
Keywords: Campi Flegrei; micro-seismic activity; rainfall triggering on micro-seismic activity; seismic